Stratifikasi Sosial dalam Novel Pabrik Karya Putu Wijaya - Awalludin Awalludin; Samsul Anam (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2019)
The purpose of this study was to describe social stratification in the novel of Pabrik written by Putu Wijaya based on the elements if its intrinsic. The method which was used in this research is descriptive method. Data analysis techniques begin with data reduction, data presentation, conclusions, and verification. Test the validity of the data in the form of expert validity test related to the results of analysis of research data. The results of the analysis of social stratification in this novel tell various problems about social stratification in the environment of a factory. Social stratification that occurs includes classes in society, criteria in the layers of society, and position or status in society that is seen based on the criteria contained in the intrinsic elements contained in the novel. Social stratification in the novel of Pabrik can be used as one of the teaching materials for Indonesian language teachers in explaining the building elements of the novel.